Peningkatan Hasil Belajar Matematika dengan Pendekatan Kontekstual pada Materi Pecahan di Kelas 3 MI Nurul Huda - Ningsih Ningsih; Yulina Fadilah (AS-SABIQUN, 2023)
In this classroom action research carried out to solve problems that occur in the learning process, it is known that the results of learning mathematics in fraction material in grade 3 are not optimal. The purpose of this study was to determine student activity in improving learning outcomes. The research subjects this time were 15 grade 3 MI Nurul Huda students, 7 male students and 8 female students. In this study, it consisted of 2 cycles, namely cycle I and cycle II. The data collection methods used in this study were: observation, interviews, tests and documentation. The results of the research on the activeness of teachers and students have increased, the activeness of teachers in cycle I was 69.23% to 86.83% in cycle II. While the results of student activity also increased in cycle I 65.38% to 88.46% in cycle II. Likewise, student learning outcomes also experienced an increase starting from the pre-cycle with an average acquisition of 65.27% and a completeness percentage of 26.67%, and experienced an increase in the first cycle with an average score of 71.26% and a completeness percentage of 60%. . And in the second cycle research obtained an average of 80.26% and 86.67% completeness percentage. In this way, it can be concluded that using a contextual approach can increase student activity and learning outcomes in learning mathematics in fractional material in class 3 students of MI Nurul Huda.